Tradisi Perhitungan Weton Dan Pengaruhnya Terhadap Keharmonisan Rumah Tangga Di Desa Sidomulyo Dalam Perspektif 'Urf - Hidayati, ST Nor; Luthfilhakim, Muhammad (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
The Qur'an and hadith do not specifically discuss the weton calculation tradition, but the people in Sidomulyo Village, Jakenan District still maintain this belief as an integral part of Javanese cultural heritage. Ideally, household harmony is measured by fulfilling the rights and obligations of husband and wife, but the majority of people in Sidomulyo Village, Jakenan District still believe in weton calculations, and this is the benchmark for household harmony. The aim of this research is to determine the tradition of calculating weton in Sidomulyo village, Jakenan subdistrict and its impact on household harmony according to 'urf rules. This study used qualitative research methods. To gain an in-depth understanding of the Weton calculation tradition, researchers conducted interviews with research subjects. This research was located in Sidomulyo Village, Jakenan District. The interview technique was conducted in depth with eight married couples using weton calculations. The results of this research show that the people of Sidomulyo Village believe in the importance of calculating the weton before getting married. They believe that calculating weton is one of the steps to seek safety and achieve harmony in the household and calculating weton for marriage, as happened in Sidomulyo Village, is considered an acceptable 'urf.